Highly Efficient Self‐Healing Multifunctional Dressing with Antibacterial Activity for Sutureless Wound Closure and Infected Wound Monitoring (Adv. Mater. 3/2022). Issue 3 (21st January 2022) - Tang, Ning; Zhang, Rongjun; Zheng, Youbin; Wang, Jing; Khatib, Muhammad; Jiang, Xue; Zhou, Cheng; Omar, Rawan; Saliba, Walaa; Wu, Weiwei; Yuan, Miaomiao; Cui, Daxiang; et al.
Abstract : Wound Healing In article number 2106842, Miaomiao Yuan, Daxiang Cui, Hossam Haick, and co‐workers report a novel self‐healing elastomer‐based multifunctional wound dressing (MFWD) with desirable mechanical robustness, biocompatibility, and antibacterial activity for effective wound management. MFWD assists in contracting wound edges, based on the excellent self‐healing ability of the elastomer, and enables tracking of the wound health status in real‐time via a set of (bio)chemical and physical sensors integrated therein.